Auditory impairment and assistive hearing sourcebook : basic consumer health information about auditory health, auditory impairment and its types, conditions that lead to auditory impairment, and assistive hearing for people with auditory impairment to lead a quality life ; along with facts about disability rights for people with auditory impairment and resources for additional help and information - 4 0 16; (Editor of health information), Hayes, Kevin; 5 (Detroit, MI : Omnigraphics, Inc., 2020)
Provides basic health information about auditory impairment, its problems and impacts, types of impairment and related disorders, with impairment caused by genetics and infections, guide for diagnosis, intervention, and treatment, and information about assistive hearing and disability rights for people with auditory impairment. Includes resources for additional help and information--
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: 2 -- 0; 6; Rehabilitation. -- Hearing impaired;Self-help devices for people with disabilities. -- 20; 20; 2